Generating High‐Fidelity Reflection Images Directly From Full‐Waveform Inversion: Hikurangi Subduction Zone Case Study. Issue 19 (7th October 2021) - Davy, Richard G.; Frahm, Laura; Bell, Rebecca; Arai, Ryuta; Barker, Daniel H. N.; Henrys, Stuart; Bangs, Nathan; Morgan, Joanna; Warner, Michael
Abstract: Full‐waveform inversion (FWI) can resolve subsurface physical properties to high resolutions, yet high‐performance computing resources have only recently made it practical to invert for high frequencies. A benefit of high‐frequency FWI is that recovered velocity models can be differentiated in space to produce high‐quality depth images (FWI images) of a comparable resolution to conventional reflection images. Here, we demonstrate the generation of high‐fidelity reflection images directly from the FWI process. We applied FWI up to 38 Hz to seismic data across the Hikurangi subduction margin. The resulting velocity models and FWI images reveal a complex faulting system, sediment deformation, and bottom‐simulating reflectors within the shallow accretionary prism. Our FWI images agree with conventional reflection images and better resolve horizons around the Pāpaku thrust fault. Thus, FWI imaging has the potential to replace conventional reflection imaging whilst also providing physical property models that assist geological interpretations. Plain Language Summary: Seismic reflection imaging has been used for decades by industry and academia to provide high‐resolution images of geological structures below the surface of the Earth. Over the last 5–10 years, the petroleum industry has increasingly used full‐waveform inversion (FWI) to recover well‐resolved seismic velocity models, which they then use to improve their reflection images. Here, we show that FWI can also produce images of comparable quality to conventional reflection images if higher frequencies are included in the inversion. Until now, limits on computational power have made inverting for higher frequencies prohibitively expensive. We demonstrate the potential of high‐frequency FWI in an application to seismic data across the shallow Hikurangi subduction margin and produce clear images of sedimentary layers and faults in the accretionary prism. Key Points: Full‐waveform inversion (FWI) using high‐frequency data produces high‐resolution velocity models that can be directly utilized to produce high‐fidelity depth images FWI images are comparable to conventional reflection images and provide high‐resolution physical property models to assist interpretation As FWI is applied to raw data, there are few subjective processing steps, making images easily reproducible for time‐lapse imaging